Combined effect of facial sweating and mounting a night vision device on helmet stability - Kim, Siyeon; Jeong, Wonyoung (Fashion and textiles, 2020)
A night vision device (NVD) equipped on a ballistic helmet violates the locational stability of a helmet, and sweating remaining inside a helmet can also reduce helmet stability. This study aimed to investigate the combined effect of sweating and mounting a NVD on helmet stability. Nine healthy males participated in the experiments which consisted of military simulated tasks and 20 min walking. Subjective evaluations containing helmet stability and comfort along with physiological measurements such as microclimate inside a helmet and sweating rate were obtained. Local sweat rate on the forehead was predicted by sweat rate on the upper back and forearm. The results showed that (1) mounting a NVD did not significantly influence on helmet stability per se before onset of sweating, however, (2) when it is combined with sweating, helmet stability reduced 50% during shooting in a prone position ( P < 0.05). (3) There was a significant correlation with helmet overall comfort and helmet stability ( r = 0.762, P < 0.05), and between helmet stability and helmet pressure ( ρ = 0.701, P < 0.05). The present study demonstrated that mounting additional devices on the helmet violates helmet stability when accompanied by sweating, even when optimized fit provided and that just tightening bands cannot be an absolute solution. This study emphasized the importance of helmet stability as a variable for evaluating helmet comfort.